Analisis Peranan Kinerja, Promosi, dan Pelayanan Radio RSPD 96,5 FM terhadap Kepuasan Masyarakat dalam Menyampaikan Informasi - Rini Sopiani; Junita Lubis; Fauziah Hanum (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
The aim of this research is to determine the influence of the performance, promotion and service of RSPD 96.5 FM Radio on public satisfaction in conveying information. This type of research is quantitative research. The sample used was 100 people, namely loyal listeners of RSPD Radio 96.5 FM. The research results show that performance, promotion and service have a positive and significant effect both partially and simultaneously. For the performance variable (X1), the value obtained was tcount (3.541) > ttable 1.661) and a significance level of 0.001 < 0.05. This means that performance partially influences community satisfaction. For the promotion variable (X2), the value obtained is tcount (2.946) > ttable (1.661) and the significance level is 0.001 < 0.05. This means that promotion partially influences public satisfaction. For service (X3), the value obtained is tcount (4,722) > ttable (1.661) and the significance level is 0.000 < 0.05. This means that service partially influences community satisfaction. The coefficient of determination test results obtained a value of 0.725. This value means that public satisfaction can be explained by performance, promotion and service by 72.5%. Meanwhile, the remaining 27.5% was influenced by other variables not examined in this research.